Teachers’ Readiness for Differentiated and Social-Emotional Learning in Vocational Schools - Samsul Komar; Supriyadi (LPPM Sekolah Tinggi Teknologi Nusantara Lampung, 2024)
This study aims to evaluate teachers’ readiness to formulate differentiated learning and social-emotional learning (SEL) at SMKN 1 West Kotaagung in 2024. Employing a descriptive qualitative approach, data were collected through structured interviews with 20 teachers selected using purposive sampling based on teaching experience, educational background, and involvement in professional development activities. The findings indicate that teachers’ readiness remains limited across several critical dimensions. Teachers continue to face difficulties in systematically identifying student differences, developing adaptive learning models and instructional media, and enhancing student learning motivation. In addition, the implementation of social-emotional learning has not been consistently integrated into classroom practices. Teachers encounter challenges in fostering positive student interactions, supporting emotional regulation, and strengthening students’ awareness of the importance of social-emotional competencies. From an interdisciplinary perspective, these findings suggest that teachers’ readiness is influenced by the interaction of pedagogical competence, psychological understanding, and instructional management capacity. The study highlights the need for systematic professional development that integrates differentiated instructional design with social-emotional pedagogy, supported by institutional policies and adequate learning resources. In the context of vocational education, strengthening teachers’ readiness is essential to ensure that learning processes not only address academic diversity but also equip students with social-emotional competencies required for successful participation in the workplace and society.